Listeria monocytogenes: possible mechanism of infection of goat uterus and its effects on uterine autophagy and cell apoptosis - Hong, Hailong; Hu, Yunhai; Shi, Siyuan; Liu, Ben; Zheng, Wenya; Bo, Ruonan; Xu, Zhongjie; Wu, Yifan; Cao, Yu (Frontiers in Veterinary Science, 2024)
Listeriosis is highly prevalent in the animal farming industry, with Listeria monocytogenes as the causative pathogen. To identify potential therapeutic targets for LM infection, we investigated the mechanisms of LM infection in goat uteri. We inoculated a group of goats with LM via jugular vein injection, isolated and raised them, and subsequently collected sterile samples of their uterine tissue after they exhibited clinical symptoms of LM infection. We used Giemsa staining, immunohistochemical staining, real-time qPCR, and Western blotting as experimental methods.First, we investigated the mechanism of Listeria monocytogenes (LM) infection in the goat uterus by examining the expression levels of listeriolysin O, E-cadherin, and tyrosine kinase c-Met in the uterus.Furthermore, we investigated the impact of LM infection on uterine autophagy and cell apoptosis. The results indicate that the injection of LM into the goats’ jugular veins leads to LM infection in the goats’ uteri. During LM survival inside the goat uterine cells, there is a significant increase in the expression levels of LLO, E-cadherin, and c-Met in the host uterine tissue. This suggests that LM may potentially infect goat uteri through the InlA/E-cadherin and InlB/c-Met pathways. Furthermore, LM infection increases the levels of apoptosis and autophagy in goat uteri. Apoptosis genes Bcl-2 and Bax, as well as autophagy-related genes LC3B, PINK1, and Parkin, exhibit varying degrees of changes in localization and expression in goat uteri, mediating the occurrence of apoptotic and autophagic responses.